Assessing the Utility of an Outpatient Exercise Program for Children With Cystic Fibrosis: A Quality Improvement Project - Adair, Dionne; Hider, Ahmad; Filbrun, Amy G.; Tapley, Chris; Bouma, Sandra; Iwanicki, Courtney; Nasr, Samya Z. (Frontiers in Pediatrics, 2022)
Children with cystic fibrosis (CF) (cwCF) suffer from inadequate weight gain, failure to thrive, and muscle weakness. The latter may be secondary to disuse atrophy (muscle wasting or reduction in muscle size associated with reduced physical activity and inflammation). Handgrip strength (HGS) is a reliable surrogate for muscle strength and lean body mass. Data from our CF center have shown an association between low HGS and forced expiratory volume in 1 s (FEV1) in cwCF. High-intensity interval training (HIIT) improves physical strength. Therefore, we devised a project to assess implementing a HIIT exercise program in the home setting, in order to improve physical strength in cwCF with HGS ≤ 50th percentile. Patients were instructed to complete 3–5 sessions of HIIT exercises per week. Wilcoxon matched-pairs signed-rank tests were used to compare HGS, FEV1, and body mass index (BMI) percentile at baseline and at a follow-up clinic visit. Follow-up was limited due to the COVID pandemic. Adherence to the HIIT regimen was poor. A total of twenty-nine cwCF participated in the program. However, a total of 13 individuals reported some form of moderate activity at follow-up and therefore constituted our final study population. There was a statistically significant increase in absolute grip strength (AGS) and FEV1 for these individuals. Even though the home HIIT protocol was not followed, the project demonstrated that moderate physical activity in cwCF can lead to significant improvement in HGS and overall physical strength.